2021
DOI: 10.5336/jcog.2021-82054
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Characteristics of Healthcare Professionals Working at COVID-19 Pandemic Clinics

Abstract: Coronavirus disease-2019 (COVID-19) pandemics infected millions of people around the world, causing thousands of deaths. In this global struggle, healthcare professionals work at the forefront. The COVID-19 pandemic period has impacted healthcare workers physically and psychologically. Healthcare workers work under stressful conditions and involve difficult decisions as ethical implications. Increased work demands on healthcare professionals conflict with their duties to family and friends, which causes psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“… 33 Other studies found that levels of dysmenorrhea were higher in women infected by COVID-19 virus. 34 …”
Section: Introductionmentioning
confidence: 99%
“… 33 Other studies found that levels of dysmenorrhea were higher in women infected by COVID-19 virus. 34 …”
Section: Introductionmentioning
confidence: 99%